The Impact of Violence on Individual Risk Preferences: Evidence from a Natural Experiment - Pamela Jakiela; Owen Ozier (Institute for the Study of Labor (IZA), 2016)
We estimate the impact of Kenya's post-election crisis on individual risk preferences. The crisis interrupted a longitudinal survey of more than five thousand Kenyan youth, creating plausibly exogenous variation in exposure to civil conflict by the time of the survey. We measure individual risk preferences using hypothetical lottery choice questions which we validate by showing that they predict migration and entrepreneurship in the cross-section. Our results indicate that the post-election violence sharply increased individual risk aversion. Immediately after the crisis, the fraction of subjects displaying extreme risk aversion increased by more than 80 percent. Findings remain robust when we use an IV estimation strategy that exploits random assignment of respondents to waves of surveying. Our results suggest that the crisis also impacted trust, social capital, and beliefs about the economy, though it did not have any detectable negative impacts on job prospects or wages.
Keywords: C91; C93; D01; D74; D81; 330; risk preferences; civil conflict; natural experiment